Cell cycle analysis in patients with Fanconi anemia from Serbia - Ćirković Sanja (Genetika, 2013)
Fanconi anemia (FA) is a rare autosomal recessive disorder, characterized by progressive bone marrow failure, chromosomal instability and cell cycle blockage in the G2 phase. The hypersensitivity of FA cells can be additionally induced with specific alkylating agents such as diepoxybutane (DEB) and mitomycin C, which is used in differential diagnosis of FA. Among 72 patients with clinical suspicion of FA, who were diagnosed at the Mother and Child Health Care Institute of Serbia “Dr Vukan Cupic” and the University Children’s Hospital (2004 - 2011), in 10 patients the diagnosis of FA was confirmed on the basis of an increased chromosome sensitivity to DEB. Five out of 10 FA patients were available for further flow cytometric analysis of cell cycle. We examined cell cycle blockage in G2 phase in untreated and with DEB treated lymphocyte cultures from FA patients and from the healthy persons, as control group. All five patients affected with FA, showed an increased DEB induced G2-phase-blockage which was over two times higher than in controls. The percentage of FA cells arrested in G2 phase was between 4,41% and 10,45% with mean value (MV) of 7,76%, but in the control group this range was lower: 1,56% - 4,11% (MV: 2.84%), with no overlapping. FA patients showed an increased spontaneous arrest in G2 phase, as well, comparing to healthy controls (MV: 14,63% vs. 5,82%). Cell cycle assay of G2 phase blockage could be used as an additional diagnostic tool for confirmation of FA in patients with clinical suspicion of this disease. [Projekat Ministarstva nauke Republike Srbije, br. 173046]